Economic Impacts of the U.S. Renewable Fuel Standard: An Ex-Post Evaluation - Taheripour, Farzad; Baumes, Harry; Tyner, Wallace E. (Frontiers in Energy Research, 2022)
This paper examines the extent to which biofuel production has been driven over time by the U.S. Renewable Fuel Standard (RFS) and the extent to which it was driven by non-RFS policies and market forces. While the RFS has played a critical role in providing a secure environment to produce and use more biofuels, at least in the 2000s, it was not the only factor that encouraged the biofuel industry to grow. While the existing literature has successfully identified the key drivers of the growth in biofuels, it basically has failed to properly quantify the impacts and contributions of each of these drivers separately. This paper develops short- and long-run economic analyses, using Partial Equilibrium (PE) and Computable General Equilibrium (CGE) models, to differentiate the economic impacts of the RFS from other drivers that have helped biofuels to grow. Results show: 1) the bulk of the ethanol production prior to 2012 was driven by what was happening in the national and global markets for energy and agricultural commodities and by the federal and sometimes state incentives for biofuel production; 2) the medium-to long-run price impacts of biofuel production were not large; 3) due to biofuel production, regardless of the drivers, real crop prices have increased between 1.1 and 5.5% in 2004–11 with only one-tenth of the price increases were assigned to the RFS, 4) for 2011–16, the long-run price impacts of biofuels were less than the time period of 2004–11, as in the second period biofuel production increased at much slower rate; 5) biofuel production, regardless of the drivers, has increased the US annual farm incomes by $8.3 billion between 2004–11 with an extra additional annual income of $2.3 billion between 2011–2016; 6) the modeling practices provided in this paper assign 28% of the expansion in farm incomes of the period of 2004–2011 and 100% of the extra additional incomes of the period of 2011–16 to the RFS.